Collection of autologous monocytes for dendritic cell vaccination therapy in metastatic melanoma patients - Nguyen, Xuan-Duc; Eichler, Hermann; Sucker, Antje; Schadendorf, Dirk; Klüter, Harald (Transfusion, 2002)
BACKGROUND: Dendritic cells (DCs) for immunotherapy of malignant melanoma can be generated from partially enriched monocytes prepared from PBMNCs. The feasibility of a single steady-state leukapheresis procedure to enrich monocytes for a complete vaccination series with up to 10 vaccinations was investigated. STUDY DESIGN AND METHODS: Thirty-eight patients (27 males and 11 females) with metastatic melanoma were enrolled in the study. All leukapheresis procedures were performed by a continuous flow method (Spectra, Cobe BCT) with a standard MNC program. RESULTS: An average of 11.7 L (range, 8-14 L) of whole blood was processed within 197.3 ± 23.7 minutes, and a mean of 13.5 ± 5.7 × 109 WBCs in a final volume of 191.0 ± 24.2 mL was collected. The MNC purity in the apheresis component was 81.5 ± 15.1 percent, from which 29.8 ± 14.7 percent were monocytes. Thus, 11.0 ± 5.0 × 109 MNCs and 3.2 ± 2.0 × 109 monocytes were collected per procedure. Linear regression analysis revealed a high correlation between the absolute number of monocytes in peripheral blood before the apheresis procedure and the number of monocytes in the collected component (r = 0.74, p < 0.0001). For the generation of DCs, 1.6 ± 0.8 × 109 MNCs were plated into culture dishes; 3.2 ± 1.8 percent of the cultured cells matured to DCs, which resulted in 56.5 ± 49.4 × 106 DCs (range, 6.3-178) per patient for the complete vaccination series. CONCLUSION: A target dose of monocytes for the complete vaccination series could be obtained by a single convenient, safe, steady-state leukapheresis procedure in each patient without the need for G-CSF mobilization. The absolute number of monocytes in peripheral blood before the apheresis procedure is the best predictive variable for the yield of monocytes in the apheresis component.